2008
DOI: 10.1021/pr8003453
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the Disulfide Proteome: Application of a Technique for the Analysis of Plant Storage Proteins as Well as Allergens

Abstract: Redox regulation plays an important role across a broad spectrum of biology. Accumulating evidence suggests that thioredoxin, a widely distributed redox enzyme, participates in the redox control of numerous target proteins, thus, playing a key role as a signaling intermediate that senses the metabolic state or environmental changes, and transmits information to induce appropriate reactions for survival. The recent development of proteomic strategies has facilitated the identification of thioredoxin targets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…It is evident from the study of their structures that disulfide bond reduction would reduce the compact folding of these storage proteins. In fact, the redox state within the PSV contributes to the regulation of storage protein degradation, illustrated in wheat (Wong et al 2004), barley (Shahpiri et al 2008) and rice (Yano and Kuroda 2008). In rice, limited proteolysis of the acidic chains of the glutelins is followed by reduction of the disulfide bonds linking the acidic to the basic chain, making the modified storage protein more accessible to subsequent rapid extensive proteolysis.…”
Section: Pathways Of Breakdown Of Other Storage Proteinsmentioning
confidence: 99%
“…It is evident from the study of their structures that disulfide bond reduction would reduce the compact folding of these storage proteins. In fact, the redox state within the PSV contributes to the regulation of storage protein degradation, illustrated in wheat (Wong et al 2004), barley (Shahpiri et al 2008) and rice (Yano and Kuroda 2008). In rice, limited proteolysis of the acidic chains of the glutelins is followed by reduction of the disulfide bonds linking the acidic to the basic chain, making the modified storage protein more accessible to subsequent rapid extensive proteolysis.…”
Section: Pathways Of Breakdown Of Other Storage Proteinsmentioning
confidence: 99%
“…As discussed in our previous review 54 , molecular specificity and expression patterns are important determinants of Trx-target specificity. In brief, site-directed mutagenesis studies 36 suggested that electrostatic interactions between Trx and target induced the following formation of their non-covalent binary complex.…”
Section: Current Challengesmentioning
confidence: 94%
“…Moreover, the knowledge obtained will be useful in developing new variety of plants/crops with improved yield, disease-resistance and cultivation suitability which should benefit developing countries. In medical studies, this knowledge may also reveal important clues to understand the mecha-JARQ 46 (4) 2012 T. Kawakami & H. Yano seed biochemistry 54 as well as food allergens 53 has been summarized in recent reviews. A comprehensive list of putative targets, as of 2009, is also available 35 .…”
Section: Introductionmentioning
confidence: 99%
“…I t i s a n important factor for stabilizing the protein conformation. In addition, oxidation-reduction of Cys residues in protein is significant to biological functions (Lee et al, 2004;Mieyal et al, 2008;Yano & Kuroda, 2008). Therefore, the assignment of disulfide bonding patterns will not only provide insights into its threedimensional structure and contribute to the understanding of its structure-function relationship but will also play a role in the regulation of fundamental cellular processes.…”
Section: In Addition It I S P O S S I B L E T H a T O U R M S S Y S mentioning
confidence: 99%